How does capital structure affect firm's market competitiveness? - Nga Thi Viet Nguyen; Nguyen Thi Kim Chi; Phuong Thi Minh Ho; Huong Thi Nguyen; Nguyen Duy Van (Cogent Economics & Finance, 2021)
Effective capital decisions not only increase the operational efficiency of businesses but also is strategic to bring the enterprise's competitive advantages to the market. Using an appropriate debt ratio helps businesses to strike a balance between internal and external resources to compete with other enterprises in the industry. This study aims to find out the effects of capital structure through debt ratio (DR) on the competitiveness of enterprises (HHI) in Vietnam. A sample of 574 companies listed on Vietnam's stock exchange from 2010-2018 is studied with STATA software. The results show that capital structure affects the competitiveness of enterprises in reverse U-shape. At the same time, DR affects HHI in the form of the U-shaped function in industrial products, information and telecommunication, and consumer goods. Meanwhile, DR affects HHI in reverse U-shape in the sectors of consumer services, raw materials, and community utilities. With the results of this analysis, the research also provides discussion as well as policy implications for businesses to make optimal use of capital structure to provide competitive advantage in the market.
Keywords: D41; G32; P12; 330; capital structure; debt ratio; market competition; market share distribution; Vietnam